2017
DOI: 10.1097/md.0000000000006145
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypothyroidism in the community

Abstract: The goal of treatment in patients with primary hypothyroidism is to attain euthyroidism guided by the stipulated thyroid-stimulating hormone (TSH) levels range so as to minimize any potential long-term adverse effects. However, various factors may result in their Levothyroxine (T4) under and over-replacement.Our study aimed to evaluate the mean daily dose of L-T4 replacement for Asian patients with primary hypothyroidism. The secondary aims were to determine the proportion of those who were either over or unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“… 6 However, when we compare the dose reported in previous studies with that obtained in our population, we confirm that the LT4 requirements to reach the euthyroid state are lower. Recent studies 16 , 17 support our finding and highlight the need for a review of current recommendations for the treatment of patients with hypothyroidism.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“… 6 However, when we compare the dose reported in previous studies with that obtained in our population, we confirm that the LT4 requirements to reach the euthyroid state are lower. Recent studies 16 , 17 support our finding and highlight the need for a review of current recommendations for the treatment of patients with hypothyroidism.…”
Section: Discussionsupporting
confidence: 80%
“…Another study demonstrated that overtreated subjects received a higher dose of LT4 than those in the euthyroid state (1.4 μg/kg/day versus 1.1 μg/kg/day). 17 Our initial analysis showed that the variables involved in the patient's overtreated (TSH <0.4 µIU/ml) were higher LT4 dose, male gender, lower BW, and higher frequency of radioiodine therapy, Hashimoto's thyroiditis, and thyroid surgery. Therefore, we performed a logistic regression analysis to evaluate the variables involved with a TSH level <0.4 µIU/ml and we observed that LT4 dose and history of thyroid surgery and Hashimoto's thyroiditis were initially associated with a greater probability of overtreatment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The dosage regimen of levothyroxine depends upon many factors, including body weight and BMI [1]. The demographic and dosing factors influence thyroid status [13]. Our study has predicted the correlation of levothyroxine dosage in primary hypothyroidism in the Pakistani population with patients' anthropometric measures like body weight and BMI.…”
Section: Discussionmentioning
confidence: 74%
“…However, weight-based L-T4 dose determination has been recommended by both the American and European thyroid associations for L-T4 initiation. Race, ethnicity (African Americans versus Caucasians), and obesity (obese versus non-obese) may influence weight-based L-T4 dose determination [1,[5][6][7][8][9][10]. Thyrotropin of less than 2.5 µIU/L was suggested as a more appropriate therapeutic target in hypothyroid patients requiring L-T4 because most healthy subjects have a TSH of less than 2.5 µIU/L [8].…”
mentioning
confidence: 99%